2015
DOI: 10.12816/0018079
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Employee Readiness for Change : Mediating Effect of Commitment to Change

Abstract: The study attempted to look at the influence of individual factors (creative behavior and practical intelligence), process factors (participation in decision making and quality of communication) and context factors (trust in management and history of change) on employee readiness for change to transformational changes. Commitment to change and its three dimensions-affective, continuance and normative were hypothesized to act as a mediator in the present study. The data was collected through a survey using self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…Based on several studies it was concluded that followership significantly moderated the relationship of leadership and employee participation in change (Khan et al, 2018), the need for changes that shape authentic behavior of employees will influence support for change (Abdel-Ghany, 2014), employees who are ensure in their abilities experience a high level of readiness to change (Vakola, 2014). Affective commitment of employees, which is characteristic of authentic followership also has to do with readiness for change (Soumyaja et al, 2015). Based on the above researches, our study proposes the following hypothesis: H4: Authentic followership has a positive influence on change readiness.…”
Section: Research Methodology and Frameworkmentioning
confidence: 99%
“…Based on several studies it was concluded that followership significantly moderated the relationship of leadership and employee participation in change (Khan et al, 2018), the need for changes that shape authentic behavior of employees will influence support for change (Abdel-Ghany, 2014), employees who are ensure in their abilities experience a high level of readiness to change (Vakola, 2014). Affective commitment of employees, which is characteristic of authentic followership also has to do with readiness for change (Soumyaja et al, 2015). Based on the above researches, our study proposes the following hypothesis: H4: Authentic followership has a positive influence on change readiness.…”
Section: Research Methodology and Frameworkmentioning
confidence: 99%
“…A thorough knowledge in employee change readiness directs the change agents to understand the best way to approach the change and the best mode to implement the change (Soumyaja, Kamlanabhan & Bhattacharyya, 2015). Susanto (2008) highlights the importance of having better judgment on individual change readiness perception prior to any change implementation.…”
Section: Employee Readinessmentioning
confidence: 99%
“…Some of those factors can be listed as, organizational commitment (Eby et al, 2000;Weber & Weber, 2001;Vakola, Tsaousis & Nikolaou, 2003;Madsen et al, 2005;Barber, 2010;Vanhala et al, 2016), trust in peers and management (Weber & Weber, 2001;Rafferty & Simons, 2006;Oreg et al, 2011;Shah, 2014), change commitment (Herscovitch & Meyer, 2002;Soumyaja et al, 2015), job satisfaction (Goulet & Singh, 2002;Robbins, 2003;Shah, 2009;Khammarnia, Ravangard & Asadi 2014;Lizar & Mangundjaya, 2014), employee empowerment and social relationship within the organization (Hanpachern et al, 1998;Cunningham et al, 2002;Madsen et al, 2005), support from peers and management (Karasek et al, 1982), teamwork (Rodriguez et al, 2015) and relationship with superiors and peers (Eby et al, 2000;Miller et al, 2006;Barber, 2010;Shah & Shah, 2010). In this article, we focus on two factors (organizational commitment and trust in peers and management) that have been intensively studied in many developed countries, but hardly in developing countries of their impact on employee readiness.…”
Section: Employee Readinessmentioning
confidence: 99%
“…At the same time, the rapid development of IT, as well as its implementation in all spheres of human life in recent years has led to a sharp expansion of information processing methods. It is impossible today to imagine an enterprise space without IT [1].…”
Section: Introductionmentioning
confidence: 99%